ANALISIS BEDA ROA, ROE, DAN BOPO BANK SWASTA DAN BANK PEMERINTAH SEBELUM DAN MASA PANDEMI COVID-19 DI INDONESIA - Naisyapuri , Yuninda; Algifari (LPPM STIE YKPN Yogyakarta, 2024)
The study aims to examine the difference in profitability between government banks and private banks before and during the Covid-19 pandemic. Government banks used Bank BNI and private banks used Bank Mega as a sample. Bank profitability is measured by ROA, ROE, and BOPO. The data used in this study are ROA, ROE, and BOPO of Bank BNI and Bank Mega quarterly data from quarter 1 of 2017 to quarter 4 of 2021. The hypothesis of this study was tested using a two-way multivariate analysis of variance (MANOVA). The results of this study conclude that there are differences in ROA, ROE, and BOPO between government banks and private banks before and during the COVID-19 pandemic. The ROA of government banks is higher than the ROA of private banks before the Covid-19 pandemic. However, during the COVID-19 pandemic, the ROA of government banks was lower than the ROA of private banks. Before the COVID-19 pandemic, the ROE of government banks was higher than the ROE of private banks. However, during the COVID-19 pandemic, the ROE of government banks was lower than the ROE of private banks. The BOPO of government banks is lower than the BOPO of private banks before the Covid-19 pandemic. However, during the Covid-19 pandemic, the BOPO of government banks was higher than the BOPO of private banks.